Evolving multidisciplinary treatment of squamous cell carcinoma of the head and neck in India✰. (2021) - Anand, A.K.; Agarwal, J.P.; D'Cruz, A.; Dattatreya, P.S.; Goswami, C.; Joshi, A.; Julka, P.K.; Noronha, V.; Prabhash, K.; Rao, R. Ranga; Kumar, Rejnish; Toprani, R.; et al.
Highlights: Evolution of a multimodal approach in the overall management of squamous cell carcinoma of the head and neck (SCCHN) especially in India. Present advances in technology (newer surgical techniques), novel medical and radiotherapy (RT) approaches; and their role for an integrated approach for treating SCCHN. Current role of immunotherapy in SCCHN. Integrated multidisciplinary approach in maximizing patient outcomes, reduction in treatment related morbidities with consequent impact on quality of life of survivors. Abstract: In this article, we highlight the evolution of a multimodal approach in the overall management of squamous cell carcinoma of the head and neck (SCCHN) in India; present advances in technology (newer surgical techniques), novel medical and radiotherapy (RT) approaches; review their roles for an integrated approach for treating SCCHN and discuss the current role of immunotherapy in SCCHN. For locally advanced (LA) SCCHN, the multidisciplinary approach includes surgery followed by RT, with or without chemotherapy (CT) or concurrent chemoradiotherapy. Improved surgical techniques of reconstruction and voice-preservation are being implemented. Advanced forms of high-precision conformal techniques like intensity-modulated radiotherapy are used to deliver highly conformal doses to tumors, sparing the surrounding normal tissue. Compared with RT alone, novel CT regimens and targeted therapeutic agents have the potential to improve locoregional control and survival and reduce treatment-induced toxicities. Several clinical trials have demonstrated efficacy, safety, and quality of life benefits of adding cetuximab to RT regimens in LASCCHN. Studies have also suggested a cetuximab-related laryngeal preservation benefit. At progression, platinum-based CT combined with cetuximab (a monoclonal anti-epidermal growth factor receptor antibody) is the only validated option available as the first-line therapy. Thus, an integrated multidisciplinary approach plays a key role in maximizing patient outcomes, reduction in treatment related morbidities that consequently impact quality of life of survivors.